Treatment of cardiac transthyretin amyloidosis: an update. (20th May 2019) - Emdin, Michele; Aimo, Alberto; Rapezzi, Claudio; Fontana, Marianna; Perfetto, Federico; Seferović, Petar M; Barison, Andrea; Castiglione, Vincenzo; Vergaro, Giuseppe; Giannoni, Alberto; Passino, Claudio; Merlini, Giampaolo
Abstract: Transthyretin (TTR) is a tetrameric protein synthesized mostly by the liver. As a result of gene mutations or as an ageing-related phenomenon, TTR molecules may misfold and deposit in the heart and in other organs as amyloid fibrils. Cardiac involvement in TTR-related amyloidosis (ATTR) manifests typically as left ventricular pseudohypertrophy and/or heart failure with preserved ejection fraction. ATTR is an underdiagnosed disorder as well as a crucial determinant of morbidity and mortality, thus justifying the current quest for a safe and effective treatment. Therapies targeting cardiac damage and its direct consequences may yield limited benefit, mostly related to dyspnoea relief through diuretics. For many years, liver or combined heart and liver transplantation have been the only available treatments for patients with mutations causing ATTR, including those with cardiac involvement. The therapeutic options now include several pharmacological agents that inhibit hepatic synthesis of TTR, stabilize the tetramer, or disrupt fibrils. Following the positive results of a phase 3 trial on tafamidis, and preliminary findings on patisiran and inotersen in patients with ATTR-related neuropathy and cardiac involvement, we provide an update on this rapidly evolving field, together with practical recommendations on the management of cardiac involvement.